Psychological Symptoms of Sydenham's Chorea - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
The psychological symptoms of 11 children with Sydenham's chorea (8 girls and 3 boys, mean age 8.4 years) were evaluated at the National Institute of Mental Health, Bethesda, MD.